Inhibition of Matrix Metalloproteinase-8 Protects Against Sepsis Serum Mediated Leukocyte Adhesion - Fang, Xiao; Duan, Shu-Fang; Hu, Zhi-Yuan; Wang, Jun-Jie; Qiu, Le; Wang, Fei; Chen, Xu-Lin (Frontiers in Medicine, 2022)
Purpose Leukocyte adhesion to vascular and matrix Metalloproteinase-8 (MMP8) expression is increased in sepsis and associated with poor prognosis in sepsis patients. This study aimed to investigate the role of MMP8 in sepsis serum mediated leukocyte adhesion. Methods Bioinformatics analysis of GSE64457 and GSE65682 was performed to evaluate the role of MMP8 in the progression of sepsis. Expression of MMP8 in blood samples from patients with sepsis was detected by qRT-PCR and ELISA. Human umbilical vein endothelial cells (HUVECs) were treated with sepsis serum, control serum, and MMP8 inhibitor. Expression of vascular cell adhesion molecule-1 (VCAM-1) and intercellular cell adhesion molecule-1 (ICAM-1) were detected by qRT-PCR and ELISA, respectively. The protein expression of total p38, phosphorylated-p38, ERK1/2, and p-ERK1/2 was detected by Western blotting. Peripheral blood mononuclear cells (PBMCs) and polymorphonuclear neutrophils (PMNs) were incubated with the treated HUVECs to calculate leukocyte adhesion. Results Four hundred and twenty-nine differentially expressed genes (DEGs) and seven hub genes between sepsis patients and healthy controls were identified. GO function analysis of DEGs and hub genes indicated that the DEGs and hub genes were mainly enriched in neutrophil activation. MMP8 was selected as a key gene with an unfavorable prognosis in sepsis patients. The mRNA and protein expression of MMP8 in blood from sepsis patients were significantly higher than controls. Leukocyte adhesion and mRNA and protein expression of VCAM-1 and ICAM-1 were significantly increased in the sepsis serum group compared to that in the control group, as was the protein expression of p-p38 and p-ERK1/2. However, the MMP8 inhibitor suppressed the leukocyte adhesion promoted by sepsis serum by decreasing the expression of VCAM-1, ICAM-1, p-p38, and p-ERK1/2. Conclusion Our study indicated that MMP8 acts as a key gene in the development of sepsis, and sepsis serum promotes leukocyte adhesion to HUVECs via MMP8, which suggest that MMP8 might be a potential therapeutic target for sepsis.